1994
DOI: 10.1007/bf00193329
|View full text |Cite
|
Sign up to set email alerts
|

Chemical modification of wood by non-formaldehyde cross-linking reagents

Abstract: The features of the reaction between sitka spruce wood and non-formaldehyde reagents, i. e. glyoxal, glutaraldehyde, and dimethylol dihydroxy ethyleneurea (DMDHEU), were investigated from the aspects of moisture adsorption and bending creep properties. To the moisture adsorption data, Hailwood-Horrobin adsorption equation was applied, and whole adsorbed water was separated into hydrated water and dissolved water which correspond to monolayer and multilayer adsorption, respectively. In the treatments with non-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 13 publications
2
7
0
Order By: Relevance
“…Therefore, the bonds which restrain the recovery are probably unstable to the drastic water soaking condition, and this result was analogous to that of creep test reported previously (Yasuda et al 1994b). However, for the specimens cured for 1 to 3 h, the recovery after boiling increased more largely than that after soaking in cold water.…”
Section: Recovery Test Of Compressed Woodsupporting
confidence: 88%
See 1 more Smart Citation
“…Therefore, the bonds which restrain the recovery are probably unstable to the drastic water soaking condition, and this result was analogous to that of creep test reported previously (Yasuda et al 1994b). However, for the specimens cured for 1 to 3 h, the recovery after boiling increased more largely than that after soaking in cold water.…”
Section: Recovery Test Of Compressed Woodsupporting
confidence: 88%
“…However, Weaver et al (1960) reported that these linkages were unstable, and we also observed that the excessive washing caused the decreases of ASE and restraining effect of creep deformation (Yasuda et al 1994b).…”
Section: Introductionsupporting
confidence: 47%
“…3c and Fig. 4a) 11,13,41,42 . The band at 1460 cm -1 caused by stretching vibration of the carbon-nitrogen (-C-N) bonds 40 increased significantly.…”
Section: Ft-ir Analysismentioning
confidence: 88%
“…Due to its two active merged aldehyde groups, it can be used to glyoxylate the lignin in cell walls or crosslink with hydroxyl groups in cellulosic materials via a hemi-acetal or acetal reaction, in the presence of a catalyst [7][8][9] . In order to improve the dimensional stability of wood, previous researchers have used glyoxal as a cross-linking agent for wood modification [10][11][12][13][14] . All the modified wood in these studies exhibited excellent dimensional stability and reduced moisture absorption compared to the unmodified wood; however, the modification did not substantially improve the hardness of the wood.…”
Section: Introductionmentioning
confidence: 99%
“…Besides wood‐inorganic composites, different approaches have been attempted for wood preservation, from chemical treatments, to coatings, to impregnations . Woods are also treated with dimethyloldihydroxy‐ethyleneurea (DMDHEU) to make them more resistant to weathering effects, termite infestation, and fungal infections, and to improve dimensional stability . DMDHEU acts as a crosslinking agent between cellulose microfibrils and is able to displace water in that interspace.…”
Section: Introductionmentioning
confidence: 99%